Effect of nano-material on the performance patterns of waste cooking biodiesel fuelled diesel engine. Issue 1 (31st December 2022) - Chandran, Jishu; Manikandan, K.; Ganesh, R.; Baskar, S.
Abstract : This work paves a way on improving the Lower efficiency and higher consumption of biodiesel on a diesel engine. Biodiesel fuelled engine emits lower emission with inferior performance. Hence this work examines the effect of adding nano-material (novel graphene oxide, GO) on biodiesel derived from waste cooking oil on engine its performance. Waste cooking oil is transesterified into waste cooking oil biodiesel (WCBD) by using alcohol (Methanol), catalysts (KOH). GO nano-material is dispersed into WCBD at 100 and 200 ppm and termed as WCBD100GO and WCBD200GO respectively. Performance experiments were conducted on a diesel engine using WCBD, WCBD100GO and WCBD200GO at the same conditions. Experimental results show that the WCBD100GO and WCBD200GO have lesser BSFC (0.3 and 0.7 kg/kWh), EGT (07–16°C) and higher BTE (0.4–1.2%) than WCBD. The improvement in the performance aspects are of WCBD is owing to the Oxygen content and catalytic activity of GO nano-materials.